2015
DOI: 10.3892/ol.2015.3108
|View full text |Cite
|
Sign up to set email alerts
|

Expression of aquaporin 5 in primary carcinoma and lymph node metastatic carcinoma of non-small cell lung cancer

Abstract: Abstract. Aquaporin 5 (AQP5), a water channel protein, is highly expressed in non-small cell lung cancer (NSCLC) tissues compared with adjacent normal tissues. AQP5 expression in lung cancer tissues is associated with a poor prognosis. The present study aimed to analyze the expression of AQP5 and investigate its role in primary and lymph node metastatic NSCLCs. An immunohistochemical labeled streptavidin-biotin method was used to determine the expression of AQP5 in 94 cases of NSCLC primary carcinoma, which in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…AQP5 have been found expressed highly in primary human glioma cells compared with normal tissue, this is in accordance with the study that reported AQPs (such as AQP1 , AQP5 and AQP8 ) have been observed in high-grade tumors of various tissues [29, 30]. It is confirmed that high expression of AQP5 was associated with tumor growth, invasion and metastasis in non-small cell lung cancer [31]. Yang et al found that AQP5 expression was increased in borderline ovarian tumors and malignant tumors compared to benign and normal ovarian tumors, and that AQP5 expression was correlated with lymph node metastasis [32].…”
Section: Discussionsupporting
confidence: 89%
“…AQP5 have been found expressed highly in primary human glioma cells compared with normal tissue, this is in accordance with the study that reported AQPs (such as AQP1 , AQP5 and AQP8 ) have been observed in high-grade tumors of various tissues [29, 30]. It is confirmed that high expression of AQP5 was associated with tumor growth, invasion and metastasis in non-small cell lung cancer [31]. Yang et al found that AQP5 expression was increased in borderline ovarian tumors and malignant tumors compared to benign and normal ovarian tumors, and that AQP5 expression was correlated with lymph node metastasis [32].…”
Section: Discussionsupporting
confidence: 89%
“…Based on the findings of relationships between heat shock, cell volume, apoptosis, and proliferation, molecules related to cell volume regulation, e.g., potassium, chloride channels, the potassium and chloride co-transporter (KCC), and AQPs, may play an important role in the anticancer effects of HT. These molecules, e.g., KCC3, and AQP5, were found to be overexpressed in human cancer samples, and were identified as prognostic factors (11)(12)(13)(14)(15)32,33). If HT regulates these molecules, targeted therapy to tumors overexpressing these molecules may become possible.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of AQPs has been detected in several types of tumors, and AQPs are receiving increasing attention as new biomarkers or therapeutic targets (9,10). Previous studies reported that the expression of AQP5 was altered in tumors of various organs such as the esophagus, lung, prostate, liver, stomach, breast, and gallbladder (11)(12)(13)(14)(15)(16)(17). The strong expression of AQP5 has been identified as a prognostic factor in human cancer samples (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…AQP5 is expressed in multiple secretory organs, including salivary glands, pancreas, and sweat glands (6,30,35). AQP5 is ectopically expressed or overexpressed in several cancers including breast (12,13) and lung cancer (7,40,51), where expression levels correlate with poor prognosis (7,13). Moreover, in prostate cancer (19,34), non-small cell lung cancer (40), colon cancer (14), and cervical cancer (49), overexpression of AQP5 correlates with metastases to lymph nodes.…”
Section: Introductionmentioning
confidence: 99%